In situ single photon confocal imaging of cardiomyocyte T-tubule system from Langendorff-perfused hearts - Chen, Biyi; Zhang, Caimei; Guo, Ang; Song, Long-Sheng (Frontiers in Physiology, 2015)
Transverse tubules (T-tubules) are orderly invaginations of the sarcolemma in mammalian cardiomyocytes. The integrity of T-tubule architecture is critical for cardiac excitation–contraction coupling function. T-tubule remodeling is recognized as a key player in cardiac dysfunction. Early studies on T-tubule structure were based on electron microscopy, which uncovered important information about the T-tubule architecture. The advent of fluorescent membrane probes allowed the application of confocal microscopy to investigations of T-tubule structure. Studies have now been extended beyond single cardiomyocytes to examine the T-tubule network in intact hearts through in situ confocal imaging of Langendorff-perfused hearts. This technique has allowed visualization of T-tubule organization in their natural habitat, avoiding the damage induced by isolation of cardiomyocytes. Additionally, it is possible to obtain T-tubule images in different subepicardial regions in a single intact heart. We review how this state-of-the-art imaging technique has provided important mechanistic insights into maturation of T-tubules in developing hearts and defined the role of T-tubule remodeling in development and progression of heart failure.